Reparations, assistance and the experience of justice: lessons from Colombia and the Democratic Republic of the Congo - Dixon, Peter J. (International journal of transitional justice, 2016)
This article is concerned with the relationship between ‘reparations’ and ‘assistance’ in transitional justice (TJ). While seemingly technical, this issue exposes fundamental tensions at the heart of TJ: between inclusive and exclusive approaches to reparative justice; between the legal strictures of redress and the complex realities of violence; and between the supposed symbolic power of reparative justice and victims’ actual experience of reparations in practice. I present two contemporary examples to demonstrate this: the International Criminal Court’s forthcoming reparations in the Democratic Republic of the Congo and Colombia’s recent reparations program for victims of its armed conflict, both of which highlight that the line between reparations and assistance can become blurry in practice. They can look similar in form, have similar impacts, be distributed through similar processes and impart similar notions of responsibility and recognition to victims. Yet, in such contexts, there will always be forms of harm, types of violence and immediate needs that fall outside the boundaries of reparations programs. Assistance measures are a useful and necessary tool to help reparations overcome these shortcomings. Depending on how they are used and communicated to victims, assistance measures can both detract from the significance of reparations and increase their reach and impact. These cases present valuable lessons about how to navigate this tension. In particular, they suggest that while practitioners should always clearly understand the differences between reparations and assistance efforts, it may be better in some cases to intentionally and carefully blur the distinction.